Midcarpal Structure Effect on Force Distribution through the Radiocarpal Joint - Wollstein, Ronit; Kramer, Aviv; Friedlander, Scott; Werner, Frederick (Journal of Wrist Surgery, 2019)
Background Wrist structure is complicated by distinct anatomical patterns. Previous studies defined radiographic wrist types based on lunate and capitate shape within the midcarpal joint. We hypothesized that these disparate structural patterns will transfer forces differently through the wrist.Objective This study aims to correlate force transferred to the distal radius and ulna with morphological measurements in cadaver arms.Methods Radiographs from 46 wrists, previously tested for force transfer between the radius and ulna, were examined. The percentage of compressive force through the distal ulna was determined by mounting load cells to the radius and ulna, while 22.2 Newton (N) tensile forces were individually applied to multiple tendons. Each wrist was tested in a neutral flexion–extension and radial-ulnar deviation position.Results Wrist type and lunate type were associated with percentage of force transfer through the ulna (p = 0.002, p = 0.0003, respectively). Percentage of force transfer was correlated with capitate circumference (p = 0.02, r = 0.34).Conclusions This study supports distinct force transfer between morphological wrist types.Clinical Relevance Understanding the mechanical significance of different structural variations in the wrist bones will improve our ability to understand wrist function and the distinctive development of wrist pathology.Level of Evidence This is a Level II study.
Keywords: force transfer; structure; midcarpal joint; ulnar variance; wrist